Новый вид рода Cremastus (Hymenoptera, Ichneumonidae) из Казахстана - Нарольский, Н.Б.; Проценко, И.А. (Вестник зоологии, 1993)
C. pokozii sp. n. is described from Kazakhstan. Type material is deposited in the Institute of Zoology, Ukrainian Academy of Sciences (Kiev).